1995
DOI: 10.1002/bjs.1800821122
|View full text |Cite
|
Sign up to set email alerts
|

Palliation of irresectable hilar cholangiocarcinoma with biliary drainage and radiotherapy

Abstract: Twelve patients with irresectable or recurrent hilar cholangiocarcinoma were treated with internal biliary drainage followed by intraluminal (iridium-192) and external-beam radiotherapy. Biliary drainage was accomplished by means of a combined surgical and interventional radiological approach. Initial biliary decompression was performed surgically by tumour resection, intrahepatic biliary enteric bypass or distal biliary-enteric anastomosis with a temporary stent. Maintenance of internal biliary drainage and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(53 citation statements)
references
References 18 publications
0
50
0
3
Order By: Relevance
“…Although RT has frequently been recommended as the main treatment for patients with unresectable hilar cholangiocarcinoma (8,9,20,24,25), the use of percutaneous biliary stenting combined with RT to treat patients with unresectable hilar cholangiocarcinoma is rarely reported. When the background of patients in the two groups was not evidently different, the median stent patency was significantly longer in the UMS+RT group than in the UMS group (326 vs. 196 days; P= 0.022).…”
Section: B Amentioning
confidence: 99%
See 1 more Smart Citation
“…Although RT has frequently been recommended as the main treatment for patients with unresectable hilar cholangiocarcinoma (8,9,20,24,25), the use of percutaneous biliary stenting combined with RT to treat patients with unresectable hilar cholangiocarcinoma is rarely reported. When the background of patients in the two groups was not evidently different, the median stent patency was significantly longer in the UMS+RT group than in the UMS group (326 vs. 196 days; P= 0.022).…”
Section: B Amentioning
confidence: 99%
“…In the previous two decades, percutaneous biliary stenting and radiotherapy (RT) were palliative care programs that were widely used for patients with unresectable hilar cholangiocarcinoma (4)(5)(6)(7)(8)(9). However, the risk of complications of percutaneous biliary stenting was increased compared with the risks of endoscopic biliary stenting (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, surgical palliation should be considered if curative resection has been excluded during laparotomy for a planned curative resection. 7 We have reported our 15-year experience with 243 patients subjected to surgery for HCCA at a single medical center with resectability rate 29% in comparison to other centers (36-56%). 8,9 this low resectability can be explained by : first the high incidence of high liver cirrhosis (42%), second most of our patients were referred from rural areas with a long history of jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Several retrospective studies demonstrated that radiotherapy prolonged survival in these patients. 10,11 However, to our knowledge, most of these studies included patients with common or distal bile duct carcinoma, who have a better prognosis than patients with hilar duct carcinoma. In 1985, Karani et al 12 reported excellent results after brachytherapy alone for hilar duct carcinoma.…”
Section: Discussionmentioning
confidence: 99%